An Eddy-diffusivity/Mass-flux Boundary Layer Parameterization Based on the TKE Equation: a Dry Convection Case Study - Soares, Pedro M. M.; Miranda, Pedro M. A.; Teixeira, J.; Siebesma, A. P. (Física de la Tierra, 2008)
An eddy-diffusivity/mass-flux (EDMF) parameterization based on the turbulent kinetic energy equation (TKE) is proposed. The diffusive term is based on a prognostic TKE equation and the massflux term also depends on the prognostic TKE in two ways: in the initialization of a rising parcel, used for the estimation of updraft ensemble properties, and in the formulation of the mass-flux coefficient, which is proportional to the vertical velocity variance. The scheme is implemented in a onedimensional version of the MesoNH model and tested for a dry convective boundary layer case, with realistic results. In particular, the EDMF-TKE closure is able to reproduce realistically the countergradient fluxes and the top-entrainment. The proposed parameterization is appealing because it leads to an integrated and unified approach to convective boundary layer parameterization, blending together concepts associated with eddy-diffusivity, mass-flux and the turbulent kinetic energy.